A Blockchain-Based Framework for Secure and Transparent Supply Chain Management with Quality Assurance Using AES Encryption and Ethereum Smart Contracts - Wu, LiuYan; Yang, Yuhua (Informatica, 2025)
Blockchain technology offers transformative potential for supply chain management by improving transparency, efficiency, and security. This paper proposes a framework that integrates blockchain with quality assurance, utilizing the Advanced Encryption Standard (AES) algorithm for data encryption, the Ethereum blockchain for decentralized architecture, and smart contracts for automation. Sales order data extracted from Walmart’s transactional database is encrypted using AES to secure sensitive information (e.g., client names, geographical data), then managed via Ethereum smart contracts that automate transactions, encryption/decryption, access control, and quality checks. The system leverages Ethereum’s peer-to-peer network for data validation and integrity. Computational experiments show AES achieves encryption and decryption times of 2.8 s and 3.2 s, respectively, outperforming RSA (6.7 s/7.3 s) and ABE (7.5 s/5.2 s) in efficiency and memory usage (0.0088 MB vs. 0.186 MB for RSA). Quality assurance metrics include 100% transaction traceability, 95% accuracy in automated quality checks, and 90% supplier compliance, surpassing traditional methods. This framework enhances operational efficiency, data security, and supply chain integrity, offering a scalable solution for Asset Management (AM), Enterprise Asset Management (EAM), and Supply Chain Management (SCM).